1995
DOI: 10.1291/hypres.18.supplementi_s65
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Free Dopamine: Physiological Variability and Pathophysiological Significance

Abstract: Dopamine (DA) is the most abundant catecholamines in human plasma and exists mostly in the sulfoconjugated form (DA sulfate), a biologically inactive metabolite. The paucity of unconjugated DA (PDA) in plasma throws doubt on its physiological significance. However, PDA, when measured with a highly sensitive radioenzymatic method, showed quite different features from norepinephrine and epinephrine in some types of clinical hypertension, lower in essential hypertension and higher in primary aldosteronism and phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The possibility that DA sulfate represents a reserve pool of free DA released by concomitant glucocorticoid increase-associated stress is supported by the findings that glucocorticoids increase free DA in man. [33][34][35] This may be due either to cortisol-induced stimulation of tyrosine hydroxylase 35 the crucial catecholamines synthesising enzyme or of sulfatase activity 36 releasing free DA from DA sulfate, When administering dexamethasone to healthy subjects we have observed 37 a decreased degree of conjugation of DA from 94 ± 2% to 81 ± 6%, P Ͻ 0.05 and NA from 89 ± 2% to 61 ± 9%, P Ͻ 0.01. It is conceivable that an alternative source of free DA would be operative only in the case of considerable cortisol increase-associated stress while moderate homeostatic adjustment to posture and high salt intake 34 could be accommodated by an increased DA synthesis and release.…”
Section: Dopamine Responses To Stressmentioning
confidence: 78%
See 3 more Smart Citations
“…The possibility that DA sulfate represents a reserve pool of free DA released by concomitant glucocorticoid increase-associated stress is supported by the findings that glucocorticoids increase free DA in man. [33][34][35] This may be due either to cortisol-induced stimulation of tyrosine hydroxylase 35 the crucial catecholamines synthesising enzyme or of sulfatase activity 36 releasing free DA from DA sulfate, When administering dexamethasone to healthy subjects we have observed 37 a decreased degree of conjugation of DA from 94 ± 2% to 81 ± 6%, P Ͻ 0.05 and NA from 89 ± 2% to 61 ± 9%, P Ͻ 0.01. It is conceivable that an alternative source of free DA would be operative only in the case of considerable cortisol increase-associated stress while moderate homeostatic adjustment to posture and high salt intake 34 could be accommodated by an increased DA synthesis and release.…”
Section: Dopamine Responses To Stressmentioning
confidence: 78%
“…75 Dopamine excess originating in neoplastic tissues includes dopamine-producing pheochromocytoma which carries less than previously suspected the connotation of malignity. 80 Hypersecretion of DA can usually be detected by elevated plasma free DA 34 and DA sulfate. 34,68 The hyperdopaminergic condition, in which outpouring of DA from the tumor overwhelms the patient's ability to conjugate, 81 is usually reflected by normo-or hypotension.…”
Section: Dopamine In Secondary Hypertension and Associated Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is known that NE increases after exercise [25], an effect on hematopoietic progenitor cell proliferative capacity remains elusive. We are the first to analyze the biologically active form [26] of free (unconjugated) NE, which is probably more relevant for an influence on CPC functionality. Benschop et al [27] and Dar et al [28] showed that increased catecholamines lead to elevated leucocytes and hematopoietic stem and progenitor cells (HSPCs) in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%